1998
DOI: 10.9750/psas.127.255.279
|View full text |Cite
|
Sign up to set email alerts
|

The excavation of Cairnwell ring-cairn, Portlethen, Aberdeenshire

Abstract: The ring-cairn was completely excavated prior to its reconstruction nearby. The site originally comprised an arc of pits, in use by the Neo period (4320±80 BP -- GU-4402) surrounding a stone circle which may have been of similar date. After a long hiatus, a pyre was burnt within the stone circle (3070±60 BP -- GU-4399). A timber enclosure, with an entrance to the south, was then erected within the stone circle and five urned cremations interred in pits in the centre of the enclosure. Later the timber enclosure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…On the route of the M74 Motorway at Stoneyburn Farm, S Lanarkshire, two small cairns covered cremation burials (Banks 1995). Developer-funded excavation at Cairnwell, Aberdeenshire, revealed a complex sequence starting in the Neolithic period (Rees 1997), in which a stone circle contained a later timber enclosure. This was eventually replaced by a Bronze Age ring cairn.…”
Section: A Summary Of the Bronze Age Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…On the route of the M74 Motorway at Stoneyburn Farm, S Lanarkshire, two small cairns covered cremation burials (Banks 1995). Developer-funded excavation at Cairnwell, Aberdeenshire, revealed a complex sequence starting in the Neolithic period (Rees 1997), in which a stone circle contained a later timber enclosure. This was eventually replaced by a Bronze Age ring cairn.…”
Section: A Summary Of the Bronze Age Evidencementioning
confidence: 99%
“…It has become the conventional wisdom that on such sites timber structures were replaced by those built out of stone, but even this may prove to be misleading. Developer-funded excavation at Cairnwell, for example, showed that at one stage in its evolution the site included a ring cairn and a timber enclosure of Middle or Late Bronze Age date (Rees 1997). Reassessment of the excavated pottery from Croft Moraig, Perth & Kinross, suggests that there a timber circle may have been constructed inside an older stone circle.…”
Section: Richard Bradleymentioning
confidence: 99%